Stimulating Learning Motivation: Application of Inquiry Method in Chemistry Lessons - Susana, Nani; Nwanya, Franklin (Journal of Chemical Learning Innovation, 2024)
Purpose of the study: This research aims to describe the improvement in students' learning motivation by applying the inquiry method in chemistry lessons for Class X at State Senior High School 1, XIII Koto Kampar District. Methodology: In this research, the subjects are the students of Class X at State Senior High School 1, XIII Koto Kampar District, consisting of 41 students. The object of this study is the implementation of the inquiry method in learning. The data obtained in this study are qualitative data, collected through observation and documentation techniques. Data collection tools include tests, observation sheets for teacher and student activities. The research procedure follows an action study framework conducted in two cycles. Each cycle comprises planning, implementation, observation, and reflection stages. The success indicators are measured by achieving predetermined motivation criteria. Main Findings: In Cycle I, the achievement of the indicators was only 16.67%, while in Cycle II, it reached 100%, meeting the targets set by the researcher. Based on these results, it can be concluded that the use of inquiry strategies effectively increases students' learning motivation in Class X of State Senior High School 1, XIII Koto Kampar District in the chemistry lesson on the fundamental laws of chemistry. Novelty/Originality of this study: This study provides novelty by showing the effectiveness of the inquiry method in increasing students' learning motivation in chemistry lessons, especially in understanding the basic laws of chemistry, in a high school environment.